Global decision support for airport performance and efficiency assessment - Baltazar, Maria (2018)
Airport benchmarking depends on airport performance and efficiency indicators, and it is an important issue for business, operational management, regulatory agencies, airlines and passengers. Using the MACBETH (Measuring Attractiveness by a Categorical Based Evaluation Technique) approach, a hierarchical additive value model is constructed with criteria weights and value scales derived from expert's judgments (obtained by an online survey) and by comparison of different reference levels and profiles of performance. This model measures airport performance and efficiency and also peer benchmarks it within a set of direct competitors or self-benchmarks itself during a specified period. GDS (Global Decision Support) model outputs, integrated into a management system, allows the identification of deficiencies requiring urgent intervention and corrective measures for its continuous improvement.